On the Waves of a Pulsating World : An Engineer's Adventures in Innovation, Education and Politics : from Russia to the West /: An Engineer's Adventures in Innovation, Education and Politics : from Russia to the West. ([2019]) - Babit︠s︡kiĭ, V. I (Vladimir Ilʹich)
No abstract available